Task-Based Language Assessment: Implications for the Language Classroom - Giraldo, Frank (GIST – Education and Learning Research Journal, 2020)
With a communicative approach to language testing, performance assessment has taken on a prominent role in testing systems around the world. Specifically, task-based assessment (TBA) is now being used to make inferences about people’s language ability and what they can do with this construct under realistic communicative scenarios. This reflection paper discusses central issues in TBA, and in doing so, it shows that TBA can be observed through a classroom-assessment lens, an idea I present as Instructional Task-Based Assessment (ITBA). The paper starts by reviewing the meaning of tasks, then discusses problems with TBA and finally offers a checklist for teachers to explore TBA in classroom contexts. I also include limitations of the proposal and conclusions